2013
DOI: 10.1093/nar/gkt671
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced mutagenesis in single-strand DNA occurs primarily at cytosines and is DNA polymerase zeta-dependent only for adenines and guanines

Abstract: Localized hyper-mutability caused by accumulation of lesions in persistent single-stranded (ss) DNA has been recently found in several types of cancers. An increase in endogenous levels of reactive oxygen species (ROS) is considered to be one of the hallmarks of cancers. Employing a yeast model system, we addressed the role of oxidative stress as a potential source of hyper-mutability in ssDNA by modulation of the endogenous ROS levels and by exposing cells to oxidative DNA-damaging agents. We report here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 46 publications
4
57
0
Order By: Relevance
“…There are several overlapping and cross-talking mechanisms among DNA repair pathways. When SSBs repair intermediates caused by oxidative damage are created and persist into S-phase, they can become DSBs during replication and then require HR or NHEJ to be repaired [1316]. The present study showed that PQ-induced DSBs were dose-dependent and, therefore, correlated with the level of oxidative stress.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…There are several overlapping and cross-talking mechanisms among DNA repair pathways. When SSBs repair intermediates caused by oxidative damage are created and persist into S-phase, they can become DSBs during replication and then require HR or NHEJ to be repaired [1316]. The present study showed that PQ-induced DSBs were dose-dependent and, therefore, correlated with the level of oxidative stress.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to BER, oxidative-stress induced DNA lesions can be repaired by nucleotide excision repair (NER) [7, 13, 14]. Both pathways generate single-strand breaks (SSBs) in DNA as repair intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevents further deleterious ROS production and subsequent damage to DNA, lipids, and other proteins [36]. Here we found that systemic S. aureus sepsis produces lung mitochondrial damage as visualized by cytoplasmic ssDNA [37]. In addition to the removal of these damaged mitochondria, the cell must also replace these organelles in order to restore cellular bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the upregulation of inflammatory cytokines IL1- β , NOS 2, and TNF- α induced methylation [4649, 51, 52, 263]. H. pylori induces oxidative stress, ROS, and RNS which can cause p53 point mutations [264267]. Nitric oxide (NO) can cause G:T mismatch during DNA synthesis and eventually results in G:C to A:T base transversion and epigenetic modification of tumorigenic genes (Figure 2) [268, 269].…”
Section: Methylationmentioning
confidence: 99%